Expert System for Detecting TBC Disease Using Web-Based Fuzzy Mamdani Method (Lung TB): Expert System for Detecting TBC Disease Using Web-Based Fuzzy Mamdani Method (Lung TB) - Ilham, Muhammad; Wahyudin, Iwan; Hidayatullah, Deny (Institute of Computer Science (IOCS), 2020)
Along with advances in technology, the expert system greatly helps the performance of doctors in detecting diseases. The purpose of the expert system that was designed was to detect TB disease, this system was made to make it easier for users to find out TB disease information with symptoms experienced by people with TB symptoms. With the application of this expert system, it is expected to be able to overcome the problems experienced by doctors or experts in conducting consultations between doctors and patients. This system is designed using PHP programming with MySQL databases and the fuzzy mamdani method which helps build the system by assessing the input and output of the system implementation results. So resulting in an idea of the existing problem that the user can find out information on tuberculosis symptoms - symptoms experienced, while the admin can change the symptoms to be updated and replace the symptom code